But For the Fear of What You Might Find Out - Anonymous (Online Ethics Center, 2006)
This case highlights potential dilemmas encountered by postdoctoral fellows in a research setting. Are participants in a breast cancer imaging modality entitled to their test results when none of the modalities have been validated as medical screening tools? This case also explores the potential problems researchers face with clinical trials.
Case Study / Scenario|Hypothetical / Fictional Case
Keywords: Human Subjects Research; Informed Consent; Public Health and Safety; Research and Practice; Safety